RECENT ADVANCES IN NANOTECHNOLOGY - BASED DRUG DELIVERY SYSTEMS FOR DELIVERY OF PHYTOCONSTITUENTS WITH SPECIAL EMPHASIS ON PSORIASIS MANAGEMENT - Deepika Rani; Vinit Kumar Sharma
Psoriasis is an inflammatory, autoimmune disorder characterized by thick and silvery lesions of the skin. Beyond its physical dimension, this disease has a significant adverse effect on quality of life and represents a huge social health burden. Based on symptoms, psoriasis may be characterized from mild to severe. A range of therapeutic agents are available to treat the disease, but none is able to provide permanent cure of the disease. The most commonly used medicines for treatment of psoriasis include anti-inflammatory drugs, steroids, biological and immunosuppressants. Though these drugs cure the disease to an extent, they are associated with many contra-indicative manifestations. Hence, an alternative system of medicine could be an excellent approach in the management of this disease, and numerous studies proved that bio-actives derived from natural sources have potential anti-psoriatic activity. Further, the therapeutic actions of these natural products can be enhanced by incorporating them in nano-formulations. The present era of medicine is focusing on implementation of natural product based nanotechnology to overcome the drawbacks of conventional treatment. This review primarily aims to focus on the recent advances in the field of natural product based nanomedicines for the effective management of psoriasis.